(untitled) (MAUSAM, 2008)
The large decrease in the ozone hole area from 2003 to 2004 and the large increase again from 2004 to 2005 and again from 2005 to 2006 cannot be explained by changes in stratospheric halogen loading but are due to interannual dynamical variability. This variability will make it difficult to detect the onset of ozone recovery in Antarctica and in particular it will be difficult to attribute any positive change in ozone to declining amounts of ozone depleting substances. In addition to analysis based on meteorological data and satellites, this paper contains results from a number of stations. Total ozone and ozonesonde data for the 2006 season have been compared to data from previous years. Several stations have observed total ozone columns that are close to the all time low for those stations. In some cases record low total ozone columns have been recorded.